2023
DOI: 10.1109/access.2023.3312711
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Traffic Flow Prediction Based on VMD and IDBO-LSTM

Ke Zhao,
Dudu Guo,
Miao Sun
et al.

Abstract: To improve the accuracy of short term traffic flow prediction and to solve the problems of nonlinearity of short term traffic flow, more noise in the data, and more difficult to determine the parametes of long short term memory networks, a combined traffic flow prediction model based on variational modal decomposition (VMD) and improved dung beetle optimization-long short term memory network (IDBO-LSTM) is proposed. First, to extract various modal components, the historical traffic flow data are smoothed using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Research by numerous scholars has demonstrated significant improvements in model prediction accuracy following the application of Variational Mode Decomposition to time-series data. For instance, Zhao et al [31] initially smoothed traffic flow data using Variational Mode Decomposition, inputted the resulting subsequences into an LSTM network prediction model, optimized the model parameters using the dung beetle algorithm (IDBO), and aggregated the subsequences' predicted values to derive final predictions. Yu et al [32] applied Variational Mode Decomposition to segment historical traffic flow data into K components, determined by varying K sample entropy values.…”
Section: Related Workmentioning
confidence: 99%
“…Research by numerous scholars has demonstrated significant improvements in model prediction accuracy following the application of Variational Mode Decomposition to time-series data. For instance, Zhao et al [31] initially smoothed traffic flow data using Variational Mode Decomposition, inputted the resulting subsequences into an LSTM network prediction model, optimized the model parameters using the dung beetle algorithm (IDBO), and aggregated the subsequences' predicted values to derive final predictions. Yu et al [32] applied Variational Mode Decomposition to segment historical traffic flow data into K components, determined by varying K sample entropy values.…”
Section: Related Workmentioning
confidence: 99%
“…Since the DBO algorithm has a good balance between global search and local development, it has significant advantages in optimizing the BPNN. The existing research shows that using DBO to optimize the initial parameters of the BPNN can improve the convergence speed of the BPNN, reduce the training time, and obtain the optimal global solution [35,36]. Although the DBO-BPNN has been applied in engineering, there is still room for improvement in this method.…”
Section: Introductionmentioning
confidence: 99%
“…The final forecasting result is the sum of the results given by all the forecasters [13][14][15]. Hybrid models have shown performance superiority not only in the renewable energy forecasting field but also in other forecasting tasks and applications, such as wave forecasting [16][17][18], stock market index prediction [19] and traffic flow prediction [20].…”
Section: Introductionmentioning
confidence: 99%